The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10854-017-7805-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel poly(aryl ether ketone) with electro-optic chromophore side chains for light modulators

Abstract: hyperpolarizabilities and ground sate dipole moments were done to understand the origin of the effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Zhang et al [120] tested a polymer specifically for AC applications with strong fields. EO polymers can exhibit very high EO coefficients of up to 300 pm V −1 [136][137][138] while the refraction index is in the order of magnitude of 2. Another example is discussed in [139], where an integrated waveguide Mach-Zehnder interferometer exploits an EO-polymer placed on a coupled micro-ring resonator.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [120] tested a polymer specifically for AC applications with strong fields. EO polymers can exhibit very high EO coefficients of up to 300 pm V −1 [136][137][138] while the refraction index is in the order of magnitude of 2. Another example is discussed in [139], where an integrated waveguide Mach-Zehnder interferometer exploits an EO-polymer placed on a coupled micro-ring resonator.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed steps of the reaction are presented in Scheme S1. The polymerization conditions employed in this study have been utilized in the preparation of numerous previously reported perfluorinated organic polymers [1,3,10,23]. As stated in the literature, the preparation of polymers containing HFB or DFB linkers was conducted under mild conditions, with relatively low temperatures not exceeding 80 • C, along with a prolonged stirring time [25].…”
Section: Nucleophilic Aromatic Substitution (Nas) and The Cross-linki...mentioning
confidence: 99%
“…PFPs possess tunable properties such as thermal and oxidative stability, hydrophobicity, lipophobicity, dielectric properties, and adjustable polarity. This enables their utilization in a diverse array of fields [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Further steps of the reaction mechanism are enclosed in Scheme S1. This polymerization methodology has been applied to prepare several reported per uorinated organic polymers [1,4,10,21]. According to literature, the polymers that contain HFB or DFB linkers were prepared under mild conditions of relatively low temperatures that did not exceed 80 °C with long stirring time [22].…”
Section: Nucleophilic Aromatic Substitution (Nas) and Cross-linking F...mentioning
confidence: 99%
“…Their synthesis has also been exploited in the polymer industry, thus enhancing the formation of new materials that possess high-temperature stability, high glass transition temperature, an anti-ammable nature, resistance to solvents, and are applicable for gas separation [7,8]. In addition, the tunable properties of FOPs include: their thermal and oxidative stability, hydrophobicity, lipophobicity, dielectric properties, and tunable polarity, allowing their usage in a wide range of applications [9,10].…”
Section: Introductionmentioning
confidence: 99%